Pengaruh Profitabilitas, Kepemilikan Manajerial dan Pertumbuhan Perusahaan Terhadap Kebijakan Utang: Studi Pada Perusahaan Manufaktur yang Terdaftar Pada Bursa Efek Indonesia dalam Tahun 2019-2013 - Muhafiz Fadly Tuanaya; Bangun Putra Prasetya (Universitas 45 Surabaya, 2024)
This research uses multiple linear analysis testing methods, using manufacturing companies listed on the IDX for the 2019-2023 period. The results show that profitability has a negative and significant influence on the company's debt policy. Managerial ownership has no influence on debt policy in manufacturing companies. This study supports the signaling theory which states that debt can be a signal to investors.